Ficolin-1 ameliorates pulmonary fibrosis via directly binding to TGF-β1 - Pengfei Gao; Yanjiao Lu; Kun Tang; Wei Wang; Tongsheng Wang; Yingwei Zhu; Jianping Zhao; Yimin Mao (Journal of Translational Medicine)
Abstract Background Ficolins were originally identified as proteins that bind to transforming growth factor-β1 (TGF-β1). They are capable of activating the complement system through lectin pathway for immune system protection. Ficolin-2 and 3 have been identified in patients with interstitial lung diseases (ILD) and their function in these diseases is currently being explored. In contrast, the functional role of ficolin-1 in pulmonary fibrosis is still elusive and remains to be elucidated. Methods The expression of ficolin-1 in the plasma of idiopathic pulmonary fibrosis (IPF) and connective tissue disease (CTD)-ILD patients was first determined. As the orthologue of human ficolin-1, ficolin-B knockout and ficolin-B overexpression were used to establish bleomycin (BLM)-induced pulmonary fibrosis mouse model. Co-immunoprecipitation, immunofluorescence and RNA sequencing were utilized to explore and expound on the expression and the functional mechanism of ficolin-1 in pulmonary fibrosis. Results Compared with healthy controls, plasma ficolin-1 was significantly decreased in patients with IPF and CTD-ILD. In the bleomycin (BLM)-induced mice model, ficolin-B deficiency aggravated lung injury and fibrosis. There was also observed increase in TGF-β1 levels and enhanced downstream signaling. However, the overexpression of ficolin-B showed preventative and therapeutic efficacy against lung fibrosis. Furthermore, coimmunoprecipitation studies revealed the direct interaction between ficolin-1 and TGF-β1 in human plasma, which was further confirmed by the colocalization of ficolin-1 and TGF-β1 in lung tissues. Conclusions Ficolin-1 inhibits pulmonary fibrosis by directly binding to the key profibrogenic factor TGF-β1, marking it as a potential target for therapy in the treatment of fibrotic lung diseases.